Strategic use of information system in Malaysia Transformer Manufacturing Sdn Bhd - A Case Study / Azman Mohd Ali - Mohd Ali, Azman (2002)
Strategic information system (SIS) is an information system that is being used by organization to gain competitive advantage. In this globalization, organization must equip them with a good SIS to keep them competitive in the market. A comprehensive SIS makes the organization realize their business goal. SIS implementation in an organization will need a full support from all level of staff especially the top management in order to succeed in the implementation. There is a lot of tool used for SIS implementation in an organization. This paper will concentrate on SIS in my organization, Malaysia Transformer Manufacturing Sdn Bhd (MTM) which is using Manufacturing Resource Planning (MRP2) from Baan Inc. This paper will discuss further on how MRP2 is been used as the tool to archive my organization planning in implementing the SIS in the organization.